Identifikasi Oksida Besi dan Pengaruh Pencucian Material Magnetik Pasir Besi Pantai Jomblom Menggunakan Metode Sonokimia - Prasdiantika, Ricka; Agustin, Niyar Candra; Rohman, Abdul (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
This study aims to prepare iron sand, determine the type of iron oxide, and determine the effect of washing iron sand with sonochemical methods. Iron sand samples were obtained from Jomblom Beach, Kendal Regency. Iron sand was separated using an external magnet to obtain magnetic material. The magnetic material obtained was washed using distilled water manually stirred and using the sonochemical method. The material was dried at 80 Â°C. Material characterization was carried out using X-Ray Fluorescence (XRF) to determine the elements contained in iron sand, Fourier Transform Infrared (FT-IR) Spectrophotometer to identify functional groups in iron sand, X-Ray Diffraction (XRD) to find out the crystal size and crystallinity of iron sand, and the Transmission Electron microscope (TEM) to determine the morphology of iron sand. The characterization results showed that the iron sand of Jomblom Beach contained Fe (72.28%), Ti (7.89%), Al (7.00%), and Si (7.60%). The iron oxide contained in the Jomblom Beach iron sand was dominated by magnetite (Fe3O4). Washing iron sand magnetic material using the sonochemical method increased the composition of the element Fe, increased the crystallinity of the magnetic material, prevented aggregation, and reduced the crystal size of the magnetic material. Magnetic material which was washed using the sonochemical method produced 79.47% Fe element, crystallinity 74.94%, and crystal size 52.78 nm.